A new genus and species of Cicadellini (Hemiptera: Cicadellidae) from the Brazilian Atlantic Rainforest - Gabriel Mejdalani; Rodney Ramiro Cavichioli (Zoologia (Curitiba), 2013)
The Neotropical sharpshooter Parasubrasaca felixi, gen. nov., sp. nov., is described and illustrated from the Atlantic Rainforest of Southeastern Brazil (state of Espírito Santo). The new genus can be distinguished from other members of the Cicadellini by several morphological features, including a unique modification of the basal portion of the aedeagus, which bears a conspicuous, ventrally directed projection that articulates with the connective. The projection bears a pair of strong spines directed posteriorly. In addition to the external morphology, color pattern, and male genitalia, the female genitalia of the new taxon are also described in detail. A discussion comparing the new genus with similar Neotropical taxa (Subrasaca Young, 1977, Soosiulus Young, 1977, Ramosulus Young, 1977, Geitogonalia Young, 1977, Ladoffa Young, 1977, and Scopogonalia Young, 1977) is provided.